2004
DOI: 10.1051/animres:2004004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defaunation on digestion and growth, in sheep receiving a mixed diet (fresh Digitaria decumbens grass and concentrate) at four protein to energy ratios

Abstract: -The effects of defaunation on growth and digestion were measured on sheep consuming four mixed diets (D1 to D4) of Digitaria decumbens grass and concentrate, with different protein to energy ratios. The protein digestible in the intestine (protein French feeding system, PDI) to energy (Forage unit, energy French feeding system) levels (P/E) in the diets were 80 (D1), 100 (D2), 120 (D3) and 140 (D4). Conventional and ciliate-free animals were conducted in parallel in 4 × 4 Latin square designs. First, two Lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(43 reference statements)
0
3
1
Order By: Relevance
“…These results indicated that feed digestion might not have been impaired by defaunation for lambs fed the oldest forage D5 diet. This is not in agreement with previous studies (Eugè ne et al, 2004b;Ushida, 1998). However, Eugè ne et al (2004b) indicated compensatory digestion of OM in the lower intestine of defaunated animals.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…These results indicated that feed digestion might not have been impaired by defaunation for lambs fed the oldest forage D5 diet. This is not in agreement with previous studies (Eugè ne et al, 2004b;Ushida, 1998). However, Eugè ne et al (2004b) indicated compensatory digestion of OM in the lower intestine of defaunated animals.…”
Section: Discussioncontrasting
confidence: 94%
“…Experimental procedure and chemical analyses The experimental procedures and chemical analyses were described in details in a previous study (Eugè ne et al, 2004b).…”
Section: Locationmentioning
confidence: 99%
“…Hess et al (2004) also found that Sapindus saponaria fruit did not increase N retention as it increased the nitrogen excretion through faeces. Inconsistent results were reported by Eugène et al (2002) and Eugène et al (2004), which showed that defaunation may or may not influence nitrogen retention depending on the diet.…”
Section: Effect On Intake Nitrogen Balance and Microbial N Supplymentioning
confidence: 83%
“…The aim of this study was to investigate the effect of defaunation and its interaction with the diet on the evolution of the cellulolytic bacterial population, the fibrolytic and amylolytic activities of microbial enzymes and the plant material degradation in the rumen. The effects of defaunation on the growth and digestion in sheep receiving the same mixed diets were published in a first article [9]. The use of oligonucleotide probes for the determination of bacterial species has generated increasing interests.…”
Section: Introductionmentioning
confidence: 99%